Magnetic Concentration of Iron in Lateritic Soils from Kamahuha, Murang’a County, in Kenya using Carbon Monoxide Generated In-Situ - Njoroge, P. W.; Mutembei, Peterson K.; Wachira, Jackson M.; Wanjau, R. (IJSET, 2014)
Chemical and Mineral Analyses of laterites from selected sites in Kamahuha area of Murang’a County, in the Republic of Kenya, have been carried out with particular interest in the levels of iron and the type of minerals the iron is present in. A laterite/charcoal mixture was heated in the temperature range 500-700OC as a slow current of air was passed through the hot mixture, the material cooled and the iron-containing mineral picked with a permanent magnet. Elemental Analysis, which was done on both the raw and concentrated samples was carried out using, Atomic Absorption Spectroscopy (AAS). The Analyses also showed that whereas the level of iron in the raw laterites was in the range 28-35, in the magnet –separated product, the level had increased to 55-62% depending on several factors such as how efficiently the laterite-charcoal mixture had been mixed and the length of time of heating.The nature of the minerals present was determined using a Brucker D2 PhaserDiffractometer. In the raw laterites, iron was present as the minerals goethite, FeO.OH and haematite, Fe2O3. These minerals have diffraction peaks at angles 2θ=21.51˚ and 2θ = 54.11, respectively. On the other hand, iron in the magnetpicked product was present predominantly as the mineral magnetite, Fe3O4, as shown by presence of a characteristic peak at 2θ = 36˚. The results of this study show that iron in laterites can be concentrated by magnetic separation after passing compressed air over hot charcoal laterite mixture.
Keywords: Hematite; Laterites; magnetic concentration; Magnetite